2015
DOI: 10.3389/fpsyg.2015.01292
|View full text |Cite
|
Sign up to set email alerts
|

Prior knowledge in recalling arguments in bioethical dilemmas

Abstract: Prior knowledge is known to facilitate learning new information. Normally in studies confirming this outcome the relationship between prior knowledge and the topic to be learned is obvious: the information to be acquired is part of the domain or topic to which the prior knowledge belongs. This raises the question as to whether prior knowledge of various domains facilitates recalling information. In this study 79 eleventh-grade students completed a questionnaire on their prior knowledge of seven different domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Taking a closer look at the similar findings from both of our studies, it appears there are not only two domains of prior knowledge relevant to recalling arguments surrounding the complex topic prenatal diagnostics. Rather, the relevance of domains depends on the group (Schmidt et al, 2015). This is important for teachers to remember when presenting and discussing bioethical dilemmas in class.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking a closer look at the similar findings from both of our studies, it appears there are not only two domains of prior knowledge relevant to recalling arguments surrounding the complex topic prenatal diagnostics. Rather, the relevance of domains depends on the group (Schmidt et al, 2015). This is important for teachers to remember when presenting and discussing bioethical dilemmas in class.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of knowledge of alcohol consumption and drug use Means and Voss (1996) reported that students with more prior knowledge of the topic generated more arguments than students with less prior knowledge. In our previous study (Schmidt, Rothgangel, & Grube, 2015) we investigated the role of prior domain-specific knowledge in recalling arguments and found that the more students had, the more arguments they were able to recall. However, this study was of a small sample.…”
mentioning
confidence: 99%
“…He used Toulmin's argument model to investigate children's and adolescents' reasoning process concerning the question of whether or not to believe in God. Similarly, within the German tradition of RE, researchers have investigated the argumentation in connection to broad science and religion debates (Schmidt et al 2015(Schmidt et al , 2017Shulman 2008) as well as the specific creation versus evolution issue (Basel et al 2013;Francis and Greer 1999;Weiß 2016). Although there is considerable research on argumentation in both science education and RE and some similar threads can be identified between these lines of research, focus on teachers and teachers' views about argumentation is particularly scarce (e.g.…”
Section: )mentioning
confidence: 99%
“…Recently, several German-speaking researchers have investigated the argumentation in RE, usually in connection with science and religion debates, e.g. Bioethics (Fuchs 2009;Schmidt, Rothgangel, and Grube 2015;Schmidt, Gruber, and Rothgangel 2017), and Creation and Evolution (Basel, Harms, and Prechtl 2013;Basel et al 2014;Weiss 2016), and are often across both subjects, drawing on the theorists set out above -or on German-language alternatives, e.g. Weiss's (2016) use of Keinpointner (1983).…”
Section: Argumentation In Religious Educationmentioning
confidence: 99%